2011
DOI: 10.1183/09031936.00005511
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of murine silica-induced lung injury and fibrosis by human embryonic stem cells

Abstract: Alveolar type II pneumocytes (ATII cells) are considered putative alveolar stem cells. Since no treatment is available to repair damaged epithelium and prevent lung fibrosis, novel approaches to induce regeneration of injured alveolar epithelium are desired.The objective of this study was to assess both the capacity of human embryonic stem cells (HUES-3) to differentiate in vitro into ATII cells and the ability of committed HUES-3 cells (HUES-3-ATII cells) to recover in vivo a pulmonary fibrosis model obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Although some studies have demonstrated the therapeutic potential of bone marrow-derived stem cells in rodent lung injury models [23,[26][27][28], there is no evidence of a role for these stem cells in populating the lung alveolar epithelium in vivo [29][30][31][32]. Recent studies have reported efficient and direct derivation of lung alveolar epithelium from murine embryonic stem cells (ESCs) [10,11,14,16] for in vitro and in vivo applications. However, immune reactions and ethical issues represent barriers to their clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have demonstrated the therapeutic potential of bone marrow-derived stem cells in rodent lung injury models [23,[26][27][28], there is no evidence of a role for these stem cells in populating the lung alveolar epithelium in vivo [29][30][31][32]. Recent studies have reported efficient and direct derivation of lung alveolar epithelium from murine embryonic stem cells (ESCs) [10,11,14,16] for in vitro and in vivo applications. However, immune reactions and ethical issues represent barriers to their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) are self-renewing pluripotent cells that can differentiate into alveolar epithelial cells in vitro [5][6][7][8][9][10][11][12][13][14][15][16]. The problems of immune rejection and ethical issues restrict clinical application of ESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study from SPITALIERI et al [110] has shown that HUES-3 can differentiate in vitro in ATII cells. Furthermore, transplantation of HUES-3-ATII into silica damaged mice significantly reduced markers of inflammation and fibrosis.…”
Section: Stem Cells In Pulmonary Fibrosismentioning
confidence: 99%
“…The anti-inflammatory and anti-fibrotic capabilities are also presented in amnion epithelial cells, placenta-derived cells, umbilical cord mesenchymal stem cells and adiposederived stem cells (ADSCs) [53][54][55][56][57][58][59]. Interestingly, ESC engraftment also ameliorates experimental pulmonary fibrosis, although clinical research using ESCs is forbidden at the current time [60,61].…”
Section: Preclinical Studies Of Stem Cells In Pulmonary Fibrosismentioning
confidence: 99%